Ambient Electrosynthesis of Ammonia: Electrode Porosity and Composition Engineering. (9th July 2018) - Wang, Hong; Wang, Lu; Wang, Qiang; Ye, Shuyang; Sun, Wei; Shao, Yue; Jiang, Zhiping; Qiao, Qiao; Zhu, Yimei; Song, Pengfei; Li, Debao; He, Le; et al.
Abstract: Ammonia, a key precursor for fertilizer production, convenient hydrogen carrier, and emerging clean fuel, plays a pivotal role in sustaining life on Earth. Currently, the main route for NH3 synthesis is by the heterogeneous catalytic Haber–Bosch process (N2 +3 H2 →2 NH3 ), which proceeds under extreme conditions of temperature and pressure with a very large carbon footprint. Herein we report that a pristine nitrogen‐doped nanoporous graphitic carbon membrane (NCM) can electrochemically convert N2 into NH3 in an acidic aqueous solution under ambient conditions. The Faradaic efficiency and rate of production of NH3 on the NCM electrode reach 5.2 % and 0.08 g m −2 h −1, respectively. Functionalization of the NCM with Au nanoparticles dramatically enhances these performance metrics to 22 % and 0.36 g m −2 h −1, respectively. As this system offers the potential to be scaled to industrial levels it is highly likely that it might displace the century‐old Haber–Bosch process.